ANCA-related vasculitis incidence and features before and during the COVID-19 pandemic in Los Angeles, Biobio Province, Chile: an observational retrospective analysis - Enos, Daniel; Hernández, Mariel; Méndez, Gonzalo P.; Cáceres, Lysis; Bravo, Ignacia; Jobet, Josefina; Castro, Simón; Cornejo, Lorena; Vega, Catalina; Salazar, Andrés (Frontiers in Nephrology, 2025)
IntroductionRenal vasculitis is a rare disease, the incidence of which increased markedly during the COVID-19 pandemic in our center. The aim of this study is to compare the incidence and the clinical and histopathological characteristics of anti-neutrophil cytoplasm antibodies (ANCA)-associated vasculitis patients before and during the COVID-19 pandemic.MethodsA single-center observational retrospective analysis of 61 patients with ANCA-associated vasculitis who were divided into two groups according to date of diagnosis: pre-pandemic from 2008 to 2020 (n=37) and during the pandemic from 2020 to the middle of 2022 (n=24). The annual incidence rate was compared, as were characteristics such as age, gender, Birmingham Vasculitis Activity Score (BVAS) score, renal clinic, organ involvement, and ANCA serotype. Biopsy findings, such as optical microscopy glomerular characteristics, crescents, interstitium, immunofluorescence, and electron microscopy findings, were analyzed. Mortality and renal replacement therapy needs were also compared.ResultsThe annual incidence rate was higher in the pandemic group compared to the pre-pandemic group, with 9.6 cases per year vs. 3.1 cases per year [incidence rate ratio (IRR)=3.11, 95% CI 1.86 to 5.20]. No significant differences between the groups were found for clinical characteristics, except for greater hemoptysis frequency in the pandemic group. Significant differences in immunofluorescence and electronic microscopy were observed, with a higher IgG deposit and C3 in the pandemic group (37.5% vs 8.1%, p=0.0064; 43.5% vs 10.8%, p=0.009, respectively), whereas the incidence of pauci-immune patterns was higher in the pre-pandemic group (81.1% vs 54.1%, p=0.016). Mortality and the need for renal replacement therapy were significant higher in the pandemic group (IRR=3.56, CI 95% 1.27–9.98 and IRR=4.24, CI 95% 2.08–8.65, respectively)ConclusionThe incidence of ANCA vasculitis increased during the COVID-19 pandemic and was associated with higher rates of IgG deposit and C3 in the immunofluorescence findings and with higher rates of deaths and dialysis in the pandemic group compared with the pre-pandemic group.